Development of BHK-21 Cell line Adapted Inactivated Newcastle Disease Vaccine - Haque, Md Enamul; Khan, Mohammed Ferdousur Rahman; Rahman, Marzia; Rahman, Md Tanvir; Saha, Sukumar; Rahman, Md Bahanur (Microbes and Health, 2014)
The present study was undertaken to isolate and characterize Newcastle disease virus (NDV) from the outbreak of layer farms for the development of BHK-21 cell adapted inactivated vaccine. A total of 6 dead birds were brought to the laboratory from the outbreak area from which 18 samples (trachea, liver and brain from each) were collected. Among them 3 samples were found positive for NDV through chicken embryo inoculation followed by HA test. The MDT, ICPI, IVPI of all isolates was 54.4, 1.56, and 2.20 respectively which revealed that the field isolates were velogenic. The isolated viruses were confirmed as NDV by reverse transcription-polymerase chain reaction (RT-PCR) using fusion gene-specific primers. The isolated virus was used to infect the BHK-21 cell line. Later the BHK-21 cell adapted viruses were used to develop oil adjuvanted inactivated vaccine and were inoculated into chickens according to vaccination schedule. The MDA was very high (112±29.62) during BCRDV vaccination, which declined quickly (88±33.12). Before vaccination with experimental vaccine, the level of antibody titre (HI) was very low (9±4.65). After vaccination at 65th day through IM, ELD50=109.7/ml with experimental vaccine, the highest HI titre in RDV vaccinated group was 160±59.25 whereas, experimental vaccinated group was 128±59.25, and control group was 7±4.65. ELISA antibody titres of all the groups were 2549.71 (RDV, LRI@0.5 ml/bird), 2450.37 (experimental@ 0.25ml/ bird), 2218.579 (experimental@ 0.50ml/bird), 2152.352 (experimental@1ml/bird) 1125.846 (control) respectively. The present study indicated that, BHK-21 cell adapted ND inactivated vaccine produced a satisfactory antibody titre along with conventional live RDV vaccine. DOI: http://dx.doi.org/10.3329/mh.v3i1.19729 Microbes and Health, June 2014. 3(1): 1-4